PERAN MEDIA PEMBELAJARAN INTERAKTIF DALAM MENINGKATKAN PEMAHAMAN SISWA TERHADAP BAHASA ARAB - Lukman, Lukman (Institut Agama Islam Pemalang (INSIP) Jawa Tengah, 2025)
This study was motivated by the lack of understanding of 4th grade students of SD Muhammadiyah Bandar Jaya towards Arabic lessons. The purpose of this study was to determine the role of interactive media in the Arabic language learning process in improving students' understanding in grade 4. By utilizing a qualitative approach with descriptive methods, this study used data collection techniques through interviews, observation, and documentation. The results of this study show that the use of interactive media can significantly improve students' understanding of Arabic. This media not only improves students' understanding but also increases students' interest in learning and encourages a more active and fun learning atmosphere. Positive impacts are also evident after the use of interactive media, such as animated videos and digital educational games that increase students' motivation and participation in the learning process. Apart from that, there are some obstacles in the application of interactive media in the form of teachers' lack of understanding of technology, less functional media tools and weak and unstable networks. It is recommended that teachers are able to utilize interactive media consistently to improve the quality of Arabic language learning. Keywords: Interactive Media, Student Understanding, Arabic Language Learning